Florida's Invaders: Exotic Pests - Center for Natural Resources (EDIS, 2003)
Florida's natural ecosystems are increasingly coming under attack by invading exotic species which displace native species, thereby degrading the diversity of floral and faunal resources. This publication was produced by the Center for Natural Resources at the University of Florida. CNR 8 is part of a Program Summary Series. First published: September 2000. Minor revision: March 2003.